Enigma unveiled: Decoding trust and relationship dynamics in the mobile banking sector of an emerging economy - Moin Ahmed Moon; Jibran Majeed; Saman Attiq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
Mobile banking, an innovative branchless banking system, is burgeoning in Pakistan. Grounded in expectation confirmation theory, this study empirically examines the interplay of trust beliefs and trustworthiness with relationship quality to generate user intentions for mobile banking. We collected data via a self-administered survey from systematically selected 346 young Generation Z (18-30) actual banking users of Pakistan. We performed structural equation modelling (SEM) via the maximum likelihood method to test the hypotheses with AMOS 25. Trust beliefs of shared value, communication, quality assurance, and integrity significantly influence cognitive and affective trust. Trustworthiness and satisfaction mediated the relationship between trust beliefs and users' intentions to use the mobile banking system in Pakistan. Policymakers and m-banking marketers should ensure quality and communicate the procedural manifestations of m- banking apps and platforms to increase trustworthiness and satisfaction with m-banking services in Pakistan. The study is a rare effort that investigates mechanisms of relationship quality to better understand consumer behavioral intentions and it identifies influential factors beneficial for financial institutions involved in offering mobile banking services.
Keywords: 330; Trustworthiness; mobile banking; behavioral intentions; trust; satisfaction; Pakistan; cognitive trust; affective trust; generation Z